Regenerasi Jamuju (Dacrycarpus imbricatus (Blume.) de Laub.) di Cagar Alam Gebugan, Kabupaten Semarang Jawa Tengah - Evananda Waskitaningtyas; Sri Utami; Erry Wiryani (Jurnal Biologi Tropika, 2018)
Gebugan Nature Reserve is one of the protected forest that still has the natural habitat of Dacrycarpus imbricatus. D. imbricatus has the potential of producing wood that is widely used by the people while the exploitation of Jamuju causes this tree species difficult to find in their natural habitat. The aim of this research was to asses D. imbricatus regeneration. The method used for taking jamuju was systematic method. The number of plots used were 15 with 10 m x 10 m area for each plot. The number of individual jamuju at the tree level, pole level, sapling level and seedling level were counted at each plot. The result of this research showed the regeneration of jamuju in Gebugan Nature Reserve was poor, indicated by tree-level individual density (5 individuals/0.15 ha = 33.3 ind/ha), pole level (not found), sapling (4 individuals/0.15 ha = 26.6 ind/ha), and seedlings (21 individuals/0.15 ha = 140 ind/ha). The environmental factors of Jamuju were found to grow at the altitude of 1,050 m asl, temperature 26.7°C to 27°C, humidity 53% to 61%, soil pH 6.3 to 7.